PENYULUHAN FIKIH BENCANA PANDEMI VIRUS CORONA (COVID-19) BAGI JAMAAH MUHAMMADIYAH KECAMATAN GONDANGLEGI - Amalia Nur Hasanah (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2022)
Purpose of the study: to realise of a comprehensive understanding of the congregation related to the Fiqh of the Corona Virus Pandemic Disaster (Covid-19) so as to minimize the negative risks that occur. Methodology: The methods used were mentoring including field studies, mentoring and socialization. Main Findings: Partners understand the importance of a thorough understanding of the congregation regarding the Fiqh of the Corona Virus Pandemic Disaster (Covid-19). Applications of this study: Increased understanding of pilgrims related to the Fiqh of the Corona Virus Pandemic Disaster (Covid-19). Novelty/Originality of this study: there were a willingness to continue to improve disaster fiqh literacy in this service, to achieve the goal of minimizing negative risks due to the impact of the COVID-19 pandemic.